2013
DOI: 10.1136/bmj.f4151
|View full text |Cite
|
Sign up to set email alerts
|

Renal outcomes associated with invasive versus conservative management of acute coronary syndrome: propensity matched cohort study

Abstract: Objectives To examine the association of early invasive management of acute coronary syndrome with adverse renal outcomes and survival, and to determine whether the risks or benefits of early invasive management differ in people with pre-existing chronic kidney disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 35 publications
0
37
0
1
Order By: Relevance
“…135 It is less clear whether this apparently favorable risk-to-benefit ratio applies to dialysis patients or would persist if revascularization were more liberally used in CKD patients. On the other hand, even among patients undergoing coronary revascularization, postprocedural use of potentially cardioprotective medications is lower in CKD patients than in those with normal kidney function, 136 suggesting that closer attention to medical regimens may improve outcomes.…”
Section: Current Management and Therapeutic Gaps Coronary Artery Diseasementioning
confidence: 99%
“…135 It is less clear whether this apparently favorable risk-to-benefit ratio applies to dialysis patients or would persist if revascularization were more liberally used in CKD patients. On the other hand, even among patients undergoing coronary revascularization, postprocedural use of potentially cardioprotective medications is lower in CKD patients than in those with normal kidney function, 136 suggesting that closer attention to medical regimens may improve outcomes.…”
Section: Current Management and Therapeutic Gaps Coronary Artery Diseasementioning
confidence: 99%
“…The concept of CI-AKI arose from observation and assumed causality, and despite a lack of rigorous hypothesis testing, has driven clinical practice for more than five decades. While a randomized controlled trial has not been conducted, there is now substantial evidence suggesting that CM contributes minimally, if at all, to the development of AKI [6,7,9,11,13,[15][16][17]. Despite the existence of such evidence, a pervasive preoccupation with what should be referred to as contrast-associated AKI (CA-AKI) persists in clinical practice, medical texts, and even among clinical researchers.…”
Section: Resultsmentioning
confidence: 99%
“…Further, a study performed in a large inpatient sample that controlled for comorbidity and acuity of illness found that patients with acute coronary syndromes (n = 1,251,812) who received CM experienced an unexpectedly lower rate of AKI as compared to patients who were not exposed to contrast (6.4% versus 17.4%) [10]. Finally, a propensity-matched cohort study of patients with non-STEMI reported one additional episode of AKI for every 62 participants treated with an early invasive approach instead of a conservative approach, with similar risks of dialysis or long-term risk of end-stage renal disease, but better long-term survival with the invasive approach [6] and in a propensitymatched cohort study of patients with STEMI, the risk of AKI was similar with and without CM exposure [7].…”
Section: Contrast Media and Acute Kidney Injury In Patients Undergoinmentioning
confidence: 99%
See 2 more Smart Citations